FIGURE 3 in Redescription and neotype designation of the Antarctic springtail Folsomotoma octooculata (Collembola: Isotomidae) - Fanciulli, Pietro Paolo; Leo, Chiara; Convey, Peter; Frati, Francesco; Carapelli, Antonio (Zenodo, 2018)
FIGURE 3. Folsomotoma octooculata; scanning electron microscopy. A, Mouth region shoWing labrum (Lbr), labium (Lbm) and maXillary outer lobe (Mol); scale bar, 20 µm; B, Labial palp With labial papilla (A, B, C, D and E); C, Ocular plate and PAO; D, Antennal organ III; E, Retinacle; F, Ventral tube. Scale bars: 20 µm (A, C, E), 10 µm (B, F), 5 µm (D). : Published as part of Fanciulli, Pietro Paolo, Leo, Chiara, Convey, Peter, Frati, Francesco & Carapelli, Antonio, 2018, Redescription and neotype designation of the Antarctic springtail Folsomotoma octooculata (Collembola: Isotomidae), pp. 392-400 in Zootaxa 4392 (2) on page 397, DOI: 10.11646/zootaxa.4392.2.11, http://zenodo.org/record/1195334